Ứng dụng cơ sở dữ liệu phân tán vào quản lí và kiểm soát hệ thống điện quốc gia - Hải, Nguyễn Nam; Lợi, Phí Mạnh (Journal of Computer Science and Cybernetics, 2016)
The paper presents an application of Distributed database into controlling and managing national electrical system. It allows to overcome some shortcomings in old system. The new system was construted in opening point of view. This point of view permits the system being easy in developing and servicing for different applications. The performance of using system is higher than the old system. The cost in developing system is cheaper than traditional approach.